Military Spending, Conflict and External Debt in Sub-Saharan Africa. Issue 4 (7th June 2019) - Dunne, J. Paul; Nikolaidou, Eftychia; Chiminya, Adonia
ABSTRACT: The damaging economic effects of the debt crises on Africa in the late 1980s encouraged considerable research on the determinants of external debt in developing economies. Although sub-Saharan Africa's (SSA) debt was cut by two-thirds by 2008, through two debt relief programmes, debt in the region has since been rising at an increasingly rapid pace. This study provides an empirical analysis of the determinants of external debt in SSA over the period 1960–2016, using dynamic panel methods. It also considers two potentially important factors that have received relatively little attention. One is military spending, rarely considered, despite a number of well-publicised scandals over the procurement of unnecessary and expensive high-tech weapons systems. A second, is the possibility that the countries studied have been involved in conflict. The empirical results point to a positive impact of military spending on external debt, but with some evidence of heterogeneity across the countries. Furthermore, findings indicate that the positive effect of military expenditure on debt becomes more marked in countries that have been affected by conflict. These results imply that policies to improve security and reduce military spending could be beneficial in reducing external debt and, potentially, improving economic performance in the region.